2007
DOI: 10.1029/2006gb002915
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties of modeling gross primary productivity over Europe: A systematic study on the effects of using different drivers and terrestrial biosphere models

Abstract: [1] Continental to global-scale modeling of the carbon cycle using process-based models is subject to large uncertainties. These uncertainties originate from the model structure and uncertainty in model forcing fields; however, little is known about their relative importance. A thorough understanding and quantification of uncertainties is necessary to correctly interpret carbon cycle simulations and guide further model developments. This study elucidates the effects of different state-of-the-art land cover and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
158
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(173 citation statements)
references
References 63 publications
15
158
0
Order By: Relevance
“…Due to different physiological principles, underlying assumptions, and amounts of input data, GPP predictions vary, sometimes significantly (Coops et al, 2009 to evaluating model principles and uncertainties of driving forcing (Cramer et al, 1999;Ito and Sasai, 2006;Jung et al, 2007;Beer et al, 2010) a systematic inter-comparison project across available GPP models is warranted to achieve mechanistic interpretation of the disagreement of GPP predictions (Ryu et al, 2011). The evaluation of water stress factors at flux sites in this study shows that the definition of water stress factors could be the reason resulting in the significant difference of trend between different GPP products, which highlights the direction of GPP model improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Due to different physiological principles, underlying assumptions, and amounts of input data, GPP predictions vary, sometimes significantly (Coops et al, 2009 to evaluating model principles and uncertainties of driving forcing (Cramer et al, 1999;Ito and Sasai, 2006;Jung et al, 2007;Beer et al, 2010) a systematic inter-comparison project across available GPP models is warranted to achieve mechanistic interpretation of the disagreement of GPP predictions (Ryu et al, 2011). The evaluation of water stress factors at flux sites in this study shows that the definition of water stress factors could be the reason resulting in the significant difference of trend between different GPP products, which highlights the direction of GPP model improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, in many regions the GPP interannual variability as simulated by LPJmL is controlled by variations of soil moisture (e.g. Jung et al, 2007;Weber et al, 2009). Soil moisture is a storage term and causes memory effects of the system, which is not taken into account by MTE.…”
Section: Performance Of Individual Trees and The Model Tree Ensemblementioning
confidence: 99%
“…Other studies have shown that the meteorological dataset used to drive LSMs is a large source of uncertainty in global land surface modelling (Hicke, 2005;Jung et al, 2007;. Different methods are used to create time series of global gridded climate data in order to drive LSMs, and this can introduce uncertainty that can propagate through model simulations (Zhao et al, 2006).…”
Section: Is the Meteorological Dataset Used To Drive The Model Importmentioning
confidence: 99%